Systematic Study of PdAuCu Alloy Nanoplasmonics for Hydrogen Gas Detection - Khairunnisa, Sarah Zulfa (My University, 2020)
Hydrogen has great potential as an important energy carrier in the future, due to its ability to generate clean and sustainable electricity in a fuel cell. However, hydrogen is flammable even at low concentration (4 vol.%) in ambient air. Furthermore, it is odorless and transparent. Therefore, hydrogen sensors are needed as a warning system for leak detection along the entire value chain. In this study, I have investigated the composition-dependent response of palladium-alloy-based plasmonic hydrogen sensors. Palladium is of interest due to its inherent selectivity towards hydrogen gas, but it also has inherent disadvantages, such as hysteretic response, and high susceptibility towards CO poisoning. To this end, it has been known that hysteresis and CO-poisoning issues can be addressed by alloying Pd with Au and Cu, and a recent study showed that a ternary alloy (PdAuCu) is able to combine the best features from both PdAu and PdCu binary alloys. However, there is a trade-off between the ternary alloy sensor’s sensitivity and CO-poisoning resistance. Therefore, in this thesis, I have systematically screened a broader Cu and Au concentration range in PdAuCu ternary alloys to find the optimum alloyant concentration in this respect. As the main results, I found that; (i) CO-poisoning resistance is achieved with a Cu content of minimum 15 at.%; (ii) hysteresis-free and linear response is obtained when the Au content is minimum 25 at.%; (iii) the identified champion systems are Pd65Au25Cu10 and Pd65Au25Cu15, which show reasonably fast response time of 6.8 and 6.1 s; and recovery time of 10.0 and 7.5 s, respectively at room temperature and in synthetic air background for 3.5 % H2.
Keywords: hydrogen sensor; plasmonic sensing; localized surface plasmon resonance; nanofabrication; hole mask colloidal lithography; hydrogen; palladium hydride; metal nanoparticle alloys